By Releasing ADP, Acanthamoeba castellanii Causes an Increase in the Cytosolic Free Calcium Concentration and Apoptosis in Wish Cells - Mattana, A. (American Society for Microbiology, 2001)
The role played by soluble molecules that may participate in acanthamoebal cytopathogenicity has yet to be fully characterized. We demonstrate here that Acanthamoeba castellanii trophozoites constitutively release ADP in the medium. Cell-free supernatants prepared from A. castellanii, by interaction with specific P(2y2) purinoceptors expressed on the Wish cell membrane, caused a biphasic rise in [Ca(2+)](i), extensive cell membrane blebbing, cytoskeletal disorganization, and the breakdown of nuclei. Cell damage induced by amoebic supernatants was blocked by the P(2y2) inhibitor Suramin. The same results were found in Wish cells exposed to purified ADP. These findings suggest that pathogenic free-living A. castellanii may have a cytopathic effect on human epithelial cells through ADP release, by a process that begins with a rise of cytosolic free-calcium concentration, and culminates in apoptosis.